Resenha: The Life Space of the Urban Child: Perspectives on Martha Muchow’s Classic Study - Flores, Eileen Pfeiffer (Psicologia: Teoria e Pesquisa, 2017)
Mey, G., & Günther, H. (Eds.). (2015). The life space of the urban child: Perspectives on Martha Muchow’s classic study. New Jersey: Transaction Publishers